IMPLIKASI APLIKASI BUJANG KURIR TERHADAP PERTUMBUHAN EKONOMI DI KOTA PONTIANAK - NIM. A1012201130, DAHLIYA (Jurnal Fatwa Hukum, 2024)
Abstract  Globalization, advances in science and technology and information have resulted in countries in the world appearing to be without borders. Various developments in knowledge and technology in a country will quickly spread and be easily accessed by people in other parts of the world.The government's role in encouraging the implementation of intellectual property rights in the bujang courier application in increasing economic growth in Pontianak City. To find out the role of the government in encouraging the implementation of intellectual property rights in the Bujang Courier application in increasing economic growth in Pontianak City. It is hoped that being able to ensure proper IPR protection, the "Bujang Courier" application can contribute more to the economic growth of Pontianak City. This can create new job opportunities, support small and medium enterprises (SMEs), and increase productivity in the logistics sector.Research methods are a way or path to obtain solutions to all problems. In research, it is known that there are several types of theories to apply one of the relevant methods to certain problems. This research is descriptive analytical in nature which aims to accurately describe the individual characteristics of a particular symptom, situation or group. Analytical descriptive research reveals laws and regulations related to the theories that are the object of their implementation in society.The Government's role in encouraging the implementation of Intellectual Property Rights (IPR) in the Bujang Courier Application in Pontianak City has a significant impact on local economic growth. The Bujang Kurir application, as an innovation in delivery services, creates added value and new economic opportunities. A foundation for better understanding the role of government in creating a business environment that is conducive to economic growth through optimizing intellectual property rights in Pontianak City.Keywords: HAKI, Bujang Courier Application.      Abstrak    Globalisasi, kemajuan ilmu pengetahuan dan teknologi serta informasi mengakibatkan negara-negara di dunia seolah tanpa sekat. Berbagai perkembangan pengetahuan dan teknologi ada di suatu negara akan dengan cepat menyebar dan mudah diakses oleh orang-orang di belahan dunia yang lain.Peran pemerintah dalam mendorong penerapan hak kekayaan intelktual pada aplikasi bujang kurir dalam meningkatkan pertumbuhan ekonomi di Kota Pontianak. Untuk mengetahui peran pemerintah dalam mendorong penerapan hak kekayaan intelktual pada aplikasi bujang kurir dalam meningkatkan pertumbuhan ekonomi di Kota Pontianak. Diharapkan mampu memastikan perlindungan HKI yang tepat, aplikasi "Bujang Kurir" dapat berkontribusi lebih besar terhadap pertumbuhan ekonomi Kota Pontianak. Hal ini dapat menciptakan peluang pekerjaan baru, mendukung usaha kecil dan menengah (UKM), dan meningkatkan produktivitas di sektor logistic.Metode penelitian merupakan suatu cara atau jalan untuk memperoleh kembali pemecahan terhadap segala permasalahan. Di dalam penelitian dikenal adanya beberapa macam teori untuk menerapkan salah satu metode relevan terhadap permasalahan tertentu. Penelitian ini bersifat deskriptif analitis yang bertujuan menggambarkan secara tepat sifat individu suatu gejala, keadaan atau kelompok tertentu. Penelitian deskriptif analitis mengungkapkan peraturan perundang-undangan yang berkaitan dengan teori-teori yang menjadi objek pelaksanaannya di dalam Masyarakat.Peran Pemerintah dalam Mendorong Penerapan Hak Kekayaan Intelektual (HAKI) pada Aplikasi Bujang Kurir di Kota Pontianak memiliki dampak yang signifikan terhadap pertumbuhan ekonomi lokal. Aplikasi Bujang Kurir, sebagai inovasi dalam layanan pengiriman, menciptakan nilai tambah dan peluang ekonomi baruLandasan untuk memahami lebih baik peran pemerintah dalam menciptakan lingkungan bisnis yang kondusif untuk pertumbuhan ekonomi melalui optimalisasi hak kekayaan intelektual di Kota Pontianak.  Kata Kunci: HAKI, Aplikasi Bujang Kurir.